Efforts to Teach Social Interaction to Autism Students in Inclusive Elementary Schools - Fitri Siti Sundari; Asep Supena (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study was to analyze efforts to teach social interaction interactions to autistic children in inclusive elementary schools. The research method used is narrative inquiry. Research subjects are children with autistic barriers in inclusive primary schools. Subjects have difficulty controlling behavior, tend not to pay attention to their interlocutor when interacting, and display repetitive behavior, moving their fingers, shouting, laughing for no apparent reason, and tantrums. Assessment of the social interaction ability of children with autistic barriers can be seen from eye contact, facial expressions, repetitive or odd movements that are less focused, lack of ability to play with friends, and emotional states such as crying or sudden anger. The form of interaction of autistic children in inclusive elementary schools leads to a form of cooperation. Subjects often work on assignments with their study groups, even though the subjects have not been able to express ideas but the subjects can help if their group friends need help. The teacher's teaching strategy in social interaction is to encourage and motivate subjects to interact with their peers. Teachers and parents work together to provide some therapy to help the subject when facing problems. The task of the assistant teacher is to help the subject complete the task according to his ability. The way to teach language and communication to the subject is by always communicating with the subject on various occasions and if speaking, it must be spoken slowly.